Transport of tropospheric and stratospheric ozone over India: Balloon-borne observations and modeling analysis. (April 2016) - Sinha, P.R.; Sahu, L.K.; Manchanda, R.K.; Sheel, V.; Deushi, M.; Kajino, M.; Schultz, M.G.; Nagendra, N.; Kumar, P.; Trivedi, D.B.; Koli, S.K.; Peshin, S.K.; et al.
Abstract: This study describes the spatio-temporal variation of vertical profiles of ozone (O3 ) measured by balloon-borne ozonesondes over two tropical sites of Trivandrum (TVM) and Hyderabad (HYD) in India from January 2009 to December 2010. In the lower troposphere, the mixing ratios of O3 over HYD (18–66 ppbv) were similar to TVM (18–65 ppbv). In the free troposphere, the O3 mixing ratios over HYD were higher than those over TVM throughout the year. In the tropical tropopause layer (TTL) region (above 15 km), the mixing ratios of O3 over TVM were higher (83–358 ppbv) compared to those measured over HYD (89–216 ppbv). Prevailing of O3 laminae between about 14 and 17 km is seen for both sites for most profiles. A strong seasonal variation of O3 is observed in the lower stratosphere between 18 and 24 km over TVM, however, it is not pronounced for HYD. Transport of air masses from the biomass burning region of the central Africa, Southeast Asia and the Indo Gangetic plains (IGP) influenced and led to enhancements of lower and mid-tropospheric O3 over HYD and TVM while, the isentropic (325 K) potential vorticity (PV) at 100 hPa showed transport of O3 –rich air from the lower stratosphere to the upper troposphere during winter and spring months over both sites. The free tropospheric O3 mixing ratios (FT-O3 ; 0–4 km) contribute substantially to the tropospheric column O3 (TCO) with an annual average fraction of 30% and reveal the similar seasonal variations over HYD and TVM. The vertical profiles of O3 obtained from the Monitoring Atmospheric Composition and Climate - Interim Implementation (MACC-II) reanalysis and the Meteorological Research Institute-Chemistry Climate Model version 2 (MRI-CCM2) are compared with the ozonesonde data over both sites. The simulated magnitude, phase and vertical gradient of O3 from both MRI-CCM2 and MACC-II are in good agreement with measurements in the stratosphere while there are significant differences in the tropospheric columns. Highlights: Balloon-borne in-situ measurement of tropospheric and stratospheric O3 over India. Role of central African and Southeast Asian air masses in tropospheric enhancements of O3 over India. Inter-comparison of vertical O3 profiles with MACC-II and CCM2 simulation. Large contribution of the FT-O3 to the tropospheric column O3 (TCO) over both sites of HYD and TVM.